TAXONOMIC ANALYSIS OF THE ALGOFLORA OF THE CHANNELS OF THE FERGANA VALLEY (in the case of JFMK, NFMK, LFMK) (Scientific journal of the Fergana State University, 2024)
In the article, a taxonomic analysis of algal flora of canals located in the Fergana Valley (in the example of SFMK, NFMK, LFMK) is presented, in which it was shown that the algoflora has a somewhat unique composition. 314 species and types of algae (218 species, 71 variations, 25 forms) belonging to 6 divisions, 12 classes, 18 orders, 34 families, and 73 genera were identified. Among them, Cyanophyta - 45, Chrysophyta - 4, Bacillariophyta - 229, Pyrrophyta - 8, Euglenophyta - 12, Chlorophyta - 16 species and species.